Single-Locus and Multi-Locus Genome-Wide Association Studies for Intramuscular Fat in Duroc Pigs - Ding, Rongrong; Yang, Ming; Quan, Jianping; Li, Shaoyun; Zhuang, Zhanwei; Zhou, Shenping; Zheng, Enqin; Hong, Linjun; Li, Zicong; Cai, Gengyuan; Huang, Wen; Wu, Zhenfang; et al. (Frontiers in Genetics, 2019)
Intramuscular fat (IMF) is an important meat trait relevant to the processing industry and consumer acceptance. To gain a better understanding of the genetic determinants of IMF, we used a composite strategy, including single-locus and multi-locus association analyses to perform genome-wide association studies (GWAS) for IMF in 1,490 Duroc boars. We estimated the genomic heritability of IMF to be 0.23 ± 0.04. A total of 30 SNPs were detected as significantly associated with IMF. Of these, five, nine, eight, and 21 significant SNPs were identified by the single-locus MLM, and multiple locus methods mrMLM, FASTmrEMMA and ISIS EM-BLASSO analyses, respectively. Interestingly, a novel quantitative trait locus (QTL) on SSC 7 was found to affect IMF. In addition, ten candidate genes (BDKRB2, GTF2IRD1, UTRN, TMEM138, DPYD, CASQ2, ZNF518B, S1PR1, GPC6 and GLI1) were found to be associated with IMF based on their potential functional roles in IMF. GO analysis showed that most of the genes were involved in muscle and organ development. A significantly enriched KEGG pathway, the sphingolipid signaling pathway, was reported to be associated with fat deposition and obesity. Identification of novel variants and candidate genes will advance our understanding of the genetic mechanisms of IMF and provide specific opportunities for marker-assisted or genomic selection in pigs. In general, such a composite single-locus and multi-locus strategy for GWAS may be useful for understanding the genetic architecture of economic traits in livestock.